2011
DOI: 10.1007/s10753-011-9329-1
|View full text |Cite
|
Sign up to set email alerts
|

Local Kappa Opioid Receptor Activation Decreases Temporomandibular Joint Inflammation

Abstract: In an attempt to decrease central side effects associated with the use of opioids, some strategies have been developed by targeting peripheral opioid receptors. In this context, kappa receptors are of major interest, since, in contrast to other opioid receptors, their activation is not associated with potent peripheral side effects. We have recently demonstrated that local activation of kappa opioid receptors significantly decreases formalin-induced temporomandibular joint nociception; however, whether it also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In the TMJ region, gonadal hormones might act on inflammatory and/or resident cells to increase the expression of β‐AR in these cells. Consistent with this idea, TMJ formalin induces inflammatory cell migration (Chicre‐Alcântara et al., ), and β‐AR are expressed in neutrophils, macrophage, eosinophils, mast cell lymphocytes, (Barnes, ) and basophile cells (Perper et al., ). Furthermore, gonadal hormone receptors are known to be expressed in inflammatory cells, as demonstrated by the presence of androgen receptor in macrophages (Fang et al., ), progesterone receptors in T lymphocyte cells (Butts et al., ) and oestradiol receptors in mast cells (Nicovani and Rudolph, ), macrophages (Capellino et al., ) and T‐cells (Tornwall et al., ).…”
Section: Discussionmentioning
confidence: 75%
“…In the TMJ region, gonadal hormones might act on inflammatory and/or resident cells to increase the expression of β‐AR in these cells. Consistent with this idea, TMJ formalin induces inflammatory cell migration (Chicre‐Alcântara et al., ), and β‐AR are expressed in neutrophils, macrophage, eosinophils, mast cell lymphocytes, (Barnes, ) and basophile cells (Perper et al., ). Furthermore, gonadal hormone receptors are known to be expressed in inflammatory cells, as demonstrated by the presence of androgen receptor in macrophages (Fang et al., ), progesterone receptors in T lymphocyte cells (Butts et al., ) and oestradiol receptors in mast cells (Nicovani and Rudolph, ), macrophages (Capellino et al., ) and T‐cells (Tornwall et al., ).…”
Section: Discussionmentioning
confidence: 75%
“…Certain mechanisms have been proposed to explain the inflammation that occurs as a result of surgical procedures, but a complete understanding of how these events are fully triggered remains unclear. Proinflammatory cytokines such as TNF-a and interleukin 1 beta (IL-1b) have often been described as important mediators in this process [10][11][12][13] . Experimental studies involving acute pain models suggest that IL-1b sensitizes nociceptors and causes hyperalgesia, therefore working actively in the pathophysiology of this type of pain [14][15][16] .…”
mentioning
confidence: 99%
“…However, peripheral KOR effects have been also demonstrated in somatic neuropathic and inflammatory pain models [4,20,24]. More recent studies showed that local KOR activation also decreases temporomandibular joint (TMJ) pain as well as inflammation and prevents the loss of alveolar bone and periodontal tissue [3,7,26,27]. …”
mentioning
confidence: 99%